Motor and Non-Motor Symptoms in Parkinson-s Disease: Effects on Quality of Life. - GÖKÇAL, ELİF; GÖKÇAL, ELİF; BABACAN YILDIZ, GÜLSEN; GÜR, VE; ASİL, TALIP; SELVITOP, R; Babacan, Yildiz; ASIL, TALİP (My University, 2017)
Introduction: This study aimed to evaluate motor and non-motor symptoms in idiopathic Parkinson's disease (IPD) patients and to determine the self-reported influence of all existing symptoms on their quality of life (QoL). Methods: The sociodemographic and clinical characteristics, medical treatments, and Modified Hoehn and Yahr (mH&Y) scores of IPD patients without cognitive impairment were recorded. A survey questioning different motor and non-motor symptoms was administered to the patients. The patients were asked to rate their symptoms by number from the greatest influence to the least influence on their QoL. Subjects were divided into two groups: those suffering from IPD for ≤5 years (Group 1) and those suffering from IPD for >5 years (Group 2). These groups were compared in terms of sociodemographic and clinical characteristics, existing symptoms, and influences of these symptoms on their QoL. Results: There were 63 patients in Group 1 and 37 patients in Group 2. No statistically significant differences were detected between the groups with respect to sociodemographic characteristics or mH&Y scores. The most common motor symptoms in both of these groups were tremor and bradykinesia; meanwhile, the non-motor symptoms most frequently encountered in these groups were pain-cramps, constipation, and excessive daytime sleepiness (EDS). Again, while the symptoms that most greatly disturbed QoL in all patients were reported to be tremor and bradykinesia, the most disturbing non-motor symptom was frequent voiding/incontinence, which was a less common symptom. Pain-cramp, constipation, and EDS, which were the most frequent non-motor symptoms, were the symptoms that least disturbed QoL. Conclusion: It is widely accepted that motor symptoms determine QoL in IPD. However, non-motor symptoms are seen during all phases of the disease. The impact of non-motor symptoms on the QoL of IPD patients remains substantial. Therefore, in addition to the well-known motor symptoms, non-motor symptoms, which may be overlooked during physical examination yet may profoundly impact QoL, should be questioned and treated appropriately to improve QoL in PD patients as much as possible.
Keywords: Parkinson’s disease; Motor symptoms; Non-motor symptoms; Quality of life